The Effect of Investment on Poverty with Economic Growth as An Intervening Variables in Central Sulawesi - Tobondo, Christina Shandra; Nurdin, Djayani; Jokolelono, Eko (International Journal of Social Sciences and Management, 2021)
This study aims to analyze the direct and indirect effects of foreign investment (PMA), domestic investment (PMDN), and government investment on poverty levels through economic growth in Central Sulawesi Province. Research explanations (explanatory research) will prove a causal relationship between the independent variable (independent variable) foreign direct investment (FDI), investment in the country (domestic), and government investment, with poverty as the dependent variable (dependent variable) with a variable economic growth as a variable intervening. The type of data used in this study is panel data (pooled data). The sampling method used purposive sampling technique. Using SEM (Structural Equation Modeling) analysis tools with the PLS (Partial Least Square) approach. The results of the first hypothesis show that there is a direct influence between foreign investment (PMA) and government investment on poverty levels in Central Sulawesi, but there is no direct influence between domestic investment (PMDN) on poverty levels in Central Sulawesi. The second hypothesis testing shows that there is an indirect effect between foreign investment, domestic investment, and government investment on poverty levels through economic growth in Central Sulawesi. Efforts to increase economic growth and reduce poverty in Central Sulawesi can be carried out through the creation of a conducive social, political, legal, and bureaucratic system, the realization of investment that is directly correlated with economic programs to alleviate poverty, and maximize the use of Corporate Social Responsibility funds. (CSR) by local governments through the body of the APBD. Int. J. Soc. Sc. Manage. Vol. 8, Issue-1: 320-332